Effect of a Ten-minute-40%-VO2max-Intensity- Ergometer-Exercise Right after Glucose Intake on the Postprandial Blood Glucose Profile among Normoglycemic Men - Hutapea, Albert M.; Octavia, Kartika (8ISC Abstract Proceedings; 8ISC Abstract Proceedings, 2022)
It is a common notion that light exercise after meals can lower postprandial hyperglycemia. This study investigated whether light exercise with an intensity of 40% VO2max can produce this effect. The study involved 30 normoglycemic men, aged (20±1.5 years), weight (59.5±9.1 kg), height (165±6.2 cm), and normal BMI (Body Mass Index). (21.8±2.8), systolic blood pressure (128.5±12.1), diastolic (90±9.9), and resting pulse (73±10.1). Both the control and the treatment groups ingested 75 grams/kg BW. The treatment group underwent a 40%-VO2maxintensity exercise using a bicycle ergometer for 10 minutes right after ingesting the glucose, but not the control group. Profiles of changes in blood glucose of both groups were recorded in all treatments at 0, 30, 60, 90, and 120 minutes after glucose intake. The Area Under Curve (AUC) of each blood glucose level was calculated using the Trapezoidal Rule method. The results showed the mean and standard deviation of the AUC in the glucose control group at 30, 60, 90, 120 minutes were 3.736.5±637, 4.757±954, 4,484.5±1.002, 3.818±716. In the exercise treatment group after glucose intake at 30, 60, 90, 120 minutes were 3,642.5±534, 4.625±1.160, 4.385.5±1.167, 3,683.5±588, respectively. The results showed that there was attenuation in the postprandial hyperglycemia in each time point but not significant (p>.05), and the overall postprandial blood glucose profile of the experimental treatment group and the glucose control group (16796±2833.1 vs. 16,336.5±3.141,6) was not significant either (p>0.05). Thus, it was concluded that exercise with an intensity of 40% VO2max performed after glucose intake did not affect postprandial blood glucose changes. It is recommended that further study be done with higher intensity and longer duration exercise. Keywords : Hyperglycemia, Postprandial Blood glucose, Ergometer, Exercise, VO2max